Sunflower WRINKLED1 plays a key role in transcriptional regulation of oil biosynthesis - Lim, Audrey R. Q. (2022)
Sunflower (Helianthus annuus) is one of the most important oilseed crops worldwide. However, the transcriptional regulation underlying oil accumulation in sunflower is not fully understood. WRINKLED1 (WRI1) is an essential transcription factor governing oil accumulation in plant cells. Here, we identify and characterize a sunflower ortholog of WRI1 (HaWRI1), which is highly expressed in developing seeds. Transient production of HaWRI1 stimulated substantial oil accumulation in Nicotiana benthamiana leaves. Dual-luciferase reporter assay, electrophoretic mobility shift assay, fatty acid quantification, and gene expression analysis demonstrate that HaWRI1 acts as a pivotal transcription factor controlling the expression of genes involved in late glycolysis and fatty acid biosynthesis. HaWRI1 directly binds to the cis-element, AW-box, in the promoter of biotin carboxyl carrier protein isoform 2 (BCCP2). In addition, we characterize an 80 amino-acid C-terminal domain of HaWRI1 that is crucial for transactivation. Moreover, seed-specific overexpression of HaWRI1 in Arabidopsis plants leads to enhanced seed oil content as well as upregulation of the genes involved in fatty acid biosynthesis. Taken together, our work demonstrates that HaWRI1 plays a pivotal role in the transcriptional control of seed oil accumulation, providing a potential target for bioengineering sunflower oil yield improvement.